Increase in the dehydrogenation rates and hydrogen-storage capacity of Mg-graphene composites by adding nickel via reactive ball milling. (October 2020) - Song, Myoung Youp; Choi, Eunho; Kwak, Young Jun
Graphical abstract: Highlights: Addition of Ni by milling in hydrogen to increase dehydrogenation rates of Mg-5graphene. Significantly higher initial hydrogenation and dehydrogenation rates than Mg-5graphene. A very high effective hydrogen-storage capacity of approximately 7 wt% at the second cycle. Increase in Mg crystallite size (decrease in the grain boundary) decreased rates with cycling. Milling and introduction of heat during cycling led to partial change of graphene to C60 fullerene. Abstract: Ni was added to increase the dehydrogenation rates of graphene-added Mg with a composition of 95 wt% Mg + 5 wt% graphene (named Mg-5graphene). For this, samples with a composition of 95 wt% Mg + 2.5 wt% Ni + 2.5 wt% graphene (named Mg-2.5Ni-2.5graphene) were prepared by ball milling in hydrogen. Mg-2.5Ni-2.5graphene had significantly higher initial hydrogenation and dehydrogenation rates, with significantly larger quantities of hydrogen absorbed and released over 60 min, than Mg-5graphene. Mg-2.5Ni-2.5graphene exhibited a very high effective hydrogen-storage capacity of approximately 7 wt% at the second cycle (n = 2). We believe that the increase in the Mg crystallite size, leading to a decrease in the grain boundaries, with cycling contributed partly to decreases in the hydrogenation and dehydrogenation rates as n increases. We attributed the partial transformation of graphene into C60 fullerene to the processing of reactive ball milling and the introduction of heat during cycling.